Nilai-Nilai Pendidikan Karakter Religious Pada Geguritan Pan Balang Tamak - Ni Nyoman Sudiani; Kadek Hemamalini; I Ketut Angga Irawan (Jayapangus Press, 2021)
To create a great nation, it is not enough to have abundant natural resources and intelligent human resources. The most important thing in building a nation is to have people with character. If the nation's children have intelligence but do not have good character then all of that will be in vain. Education has a goal to educate and shape people with character, especially religious characters. This article aims to examine the values ​​of religious character education in Geguritan Pan Balang Tamak which is carried out through discourse analysis. The values ​​of religious character education found in Geguritan Pan Balang Tamak are Satya Hredaya, Believe in Atman, Believe in death, Believe in Hyang Widhi (Brahman), and observant in praying. Through Geguritan Pan Balang Tamak, people learn religious characters so that in everyday life they can apply Hindu teachings. The contribution of this article is that all Hindus are always obedient to preserve and learn the arts and culture that have been inherited by their ancestors and all of that is also in accordance with the wishes of Hindus in Bali, especially to carry out a steady Bali.